Customized patterned substrates for highly versatile correlative light-scanning electron microscopy - Benedetti, Lorena; Sogne, Elisa; Rodighiero, Simona; Marchesi, Davide; Milani, Paolo; Francolini, Maura (Scientific reports, 2014)
Correlative light electron microscopy (CLEM) combines the advantages of light and electron microscopy, thus making it possible to follow dynamic events in living cells at nanometre resolution. Various CLEM approaches and devices have been developed, each of which has its own advantages and technical challenges. We here describe our customized patterned glass substrates, which improve the feasibility of correlative fluorescence/confocal and scanning electron microscopy.